Organizational Diagnosis of Hybrid Work Effectiveness Among Generation Z: A Systematic Literature Review - Nova Eka Wulandari; Nathalie Felicia Theandra; Nafingatun Nadziroh (Journal of Comprehensive Science, 2026)
The COVID-19 pandemic has permanently shifted organizations toward hybrid work, yet its effectiveness for Generation Z employees remains underexplored from a systemic diagnostic perspective. This systematic literature review examines the impact of hybrid work on organizational effectiveness among Generation Z employees. A search across SagePub, Google Scholar, and Scopus yielded 124 records; after screening, 13 open-access articles published between 2021 and 2026 met the inclusion criteria. The findings show that hybrid work positively influences retention, work-life balance, engagement, well-being, and job satisfaction. Work flexibility and hybrid work models emerged as the most dominant factors, followed by leadership and organizational culture. The results extend Self-Determination Theory and the Job Demands-Resources model by highlighting perceived autonomy and digital-context demands as key mechanisms. Practically, organizations should design flexible, autonomy-supportive, and inclusive work environments to attract and retain Gen Z talent. This systematic literature review synthesizes evidence from 13 studies on hybrid work effectiveness for Generation Z. The findings consistently demonstrate that hybrid work, when implemented with flexibility, autonomy, and supportive leadership, enhances retention, work-life balance, engagement, well-being, and job satisfaction.